Interstitial long-arm deletion of chromosome 7 and ectrodactyly - Tajara, E. H.; Varella-Garcia, M.; Tonelli Gusson, A. C. (Wiley, 1989)
An interstitial deletion of 7q21 was found in a boy with mental retardation, microcephaly, convergent strabismus, micrognathia, genital anomalies, and other findings, including ectrodactyly.
Keywords: chromosome 7q; chromosome deletion 7; cytology; ectrodactyly; heredity; infant; mental retardation malformation syndrome; microcephaly; micrognathia; partial monosomy 7; priority journal; Abnormalities, Multiple; Case Report; Chromosome Deletion; Chromosomes, Human, Pair 7; Clubfoot; Fingers; Mental Retardation; Support, Non-U.S. Gov't; Syndrome; Toes